Reproductive Isolation Between Taxonomically Controversial Forms of the Gray Voles (Microtus, Rodentia; Arvicolinae): Cytological Mechanisms and Taxonomical Implications - Bikchurina, Tatiana I.; Golenishchev, Fedor N.; Kizilova, Elena A.; Mahmoudi, Ahmad; Borodin, Pavel M. (Frontiers in Genetics, 2021)
The formation of hybrid sterility is an important stage of speciation. The voles of the genus Microtus, which is the most speciose genus of rodents, provide a good model for studying the cytological mechanisms of hybrid sterility. The voles of the “mystacinus” group of the subgenus Microtus (2n = 54) comprising several recently diverged forms with unclear taxonomic status are especially interesting. To resolve the taxonomic status of M. mystacinus and M. kermanensis, we crossed both with M. rossiaemeridionalis, and M. kermanensis alone with M. arvalis “obscurus” and M. transcaspicus and examined the reproductive performance of their F1 hybrids. All interspecies male hybrids were sterile. Female M. kermanensis x M. arvalis and M. kermanensis x M. transcaspicus hybrids were sterile, too. Therefore, M. mystacinus, M. kermanensis and M. rossiaemeridionalis could be considered valid species. To gain an insight into the cytological mechanisms of male hybrid sterility, we carried out a histological analysis of spermatogenesis and a cytological analysis of chromosome synapsis, recombination and epigenetic chromatin modifications in the germ cells of the hybrids using immunolocalization of key meiotic proteins. The hybrids showed wide variation in the onset of spermatogenesis arrest stage, from mature (although abnormal) spermatozoa to spermatogonia only. Chromosome asynapsis was apparently the main cause of meiotic arrest. The degree of asynapsis varied widely across cells, individuals and the crosses – from partial asynapsis of several small bivalents to complete asynapsis of all chromosomes. The asynapsis was accompanied by a delayed repair of DNA double-strand breaks marked by Rad51 antibodies and silencing of unpaired chromatin marked by γH2A.X antibodies. Overall, the severity of disturbances in spermatogenesis in general and in chromosome synapsis in particular increased in the hybrids with an increase in the phylogenetic distance between their parental species.